Correction of renal dysfunction in patients with the decompensated course of cirrhosis - A. S. Tugushev; D. I. Mikhantyev; V. V. Neshta; V. P. Akinshin; A. N. Kaulko; A. N. Petrash (Zaporožskij Medicinskij Žurnal)
Aim. Elaboration of the uniform tactical installations concerning questions of rational therapy of patients with renal dysfunction in cirrhosis and its complications is actual.